2016
DOI: 10.2514/1.c033535
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Flexible Wings with Distributed Flaps at Off-Design Conditions

Abstract: An efficient process to aerodynamically optimize transport wings while addressing static aeroelastic effects is presented. The process is used to assess the aerodynamic performance benefits of a full-span trailing-edge flap system on a generic transport aircraft at off-design conditions. To establish a proper baseline, a transport wing is first aerodynamically optimized at a midcruise flight condition. The optimized wing is then analyzed at several offdesign cruise conditions. The aerodynamic optimization is r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…The aerodynamic analysis and design tools used to complete the trade study of the distributed flap system are identical to those used in past work. 4 In this section, the static aeroelastic analysis method 12 previously developed by the authors is summarized. This method was then incorporated within a proven optimization framework 13 to allow for aerodynamic design that includes aeroelastic effects.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The aerodynamic analysis and design tools used to complete the trade study of the distributed flap system are identical to those used in past work. 4 In this section, the static aeroelastic analysis method 12 previously developed by the authors is summarized. This method was then incorporated within a proven optimization framework 13 to allow for aerodynamic design that includes aeroelastic effects.…”
Section: Methodsmentioning
confidence: 99%
“…While the method has mostly been applied to rigid geometries, the authors have extended the framework to accommodate static aeroelastic effects. 4 With some minor enhancements, the aeroelastic analysis algorithm described in Figure 1 has been used to perform aerodynamic shape optimization of flexible wings with a fixed structural layout. The loosely-coupled analysis method was wrapped within an iterative loop as shown in Figure 2.…”
Section: B Aerodynamic Shape Optimization With Aeroelastic Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that Variable Camber Continuous Trailing-edge Flaps (VCCTF) (25) can be rotated to optimal patterns for load relief (and thus achieving a lighter-weight wingbox) at The Aeronautical Journal symmetric and roll manoeuvres (26) , and/or to improve fuel burn and to mitigate flutter (27,28) of an all-metallic variant of the NASA Common Research Model (29) subjected to stresses, buckling, flutter and actuator constraints. There has also been interest in evaluating potential benefits of trailing-edge control devices for minimum drag (30,31) , particularly in cruise and in off-design conditions (32,33) .…”
Section: Introductionmentioning
confidence: 99%